SUBSURFACE STRUCTURE MODELLING OF AGUNG VOLCANO AND BATUR VOLCANO USING GRAVITY METHOD - Rahman F S, Alif
Indonesia is an archipelago arc located at the confluence of three plates, the Eurasian, Indo-Australian and Pacific plates. Interaction between the three plates take part in volcanic formation in Indonesia. Subduction between plates also results in melting of the earth's crust into magma. Magma differentiates when it moves to the surface, the process forms magma chambers and plays a role in the formation of volcanoes. The dimensions of the magma chamber can affect the eruption strength of a volcano. The geometry model of the magma chamber can be created and can be used as material for further research in disaster mitigation. The method used to model the magma chamber geometry in this study is the gravity method. The gravity method is one of the geophysical methods that can be used to determine subsurface images. Variations in the measured gravitational field can be interpreted to determine geometry and density causing the variation of gravitational field. Density contrast becomes the parameter of the existence of anomalies in the gravitational field caused by the presence of fluid, including one of them is the presence of magma. The object of this study are Agung Volcano and Batur Volcano. The model is made from printed Bali Complete Bouguer Anomaly Map, then the map is digitized and the regional and residual anomaly is separated. Modeling is done by using residual anomaly data by observing topography, geology, and other available geophysical data. Generated model indicated that the Agung Volcano magma chamber is located at a depth of about 3000 meters to more than 5000 meters from sea level. While the Batur Volcano magma chamber is located at a depth of 2500 meters to 4000 meters from sea level. From the model, Agung Volcano magma chamber was found to be larger than the magma chamber of Batur Volcano.